Future Exploration Greenhouse Design of the EDEN ISS Project - Zabel, Paul; Bamsey, Matthew; Zeidler, Conrad; Vrakking, Vincent; Schubert, Daniel; Romberg, Oliver (47th International Conference on Environmental Systems, 2017)
Paul Zabel, German Aerospace Center (DLR), Germany Matthew Bamsey, German Aerospace Center (DLR), Germany Conrad Zeidler, German Aerospace Center (DLR), Germany Vincent Vrakking, German Aerospace Center (DLR), Germany Daniel Schubert, German Aerospace Center (DLR), Germany Oliver Romberg, German Aerospace Center (DLR), Germany ICES204: Bioregenerative Life Support The 47th International Conference on Environmental Systems was held in South Carolina, USA on 16 July 2017 through 20 July 2017 The Future Exploration Greenhouse (FEG) is the heart of the international EDEN ISS project, which aims to investigate and validate techniques for plant cultivation in future bioregenerative life support systems. The EDEN ISS project partners designed and built the Mobile Test Facility (MTF), which consists of two modified 20 foot shipping containers. The FEG is integrated into one of these containers. It has a shelf-like plant cultivation system with up to four levels for growing plants and it has a cultivation area of roughly 12.5 m². The FEG is designed to accommodate differ-ent plant species ranging from leafy greens (e.g. lettuce, spinach) to tall growing plants (e.g. tomato, cucumber). The plants grow in customized trays which hold the plants in position and contain the plants’ roots. The trays can be connected to one of the two nutrient solution supply lines, each line providing a different nutrient mix. All plants grow in the same atmosphere and water-cooled LED lamps provide the light energy for photosynthesis. The FEG design has evolved from early designs in 2014 over the preliminary design by the end of 2015 to the final design which is described in this paper. Following assembly, integration and testing, the complete MTF will be shipped in October 2017 to Antarctica, where it will arrive in December 2017 and undergo a 12 month space analogue mission.